The Impact of R&D Intensity on Demand for Specialist Auditor Services* - GODFREY, JAYNE M.; HAMILTON, JANE (Contemporary Accounting Research, 2005)
The audit fee research literature argues that auditors' costs of developing brand name reputations, including top‐tier designation and recognition for industry specialization, are compensated through audit fee premiums. Audited firms reduce agency costs by engaging high‐quality auditors who monitor the levels and reporting of discretionary expenditures and accruals. In this study we examine whether specialist auditor choice is associated with a particular discretionary expenditure ‐ research and development (R&D). For a large sample of U.S. companies from a range of industries, we find strong evidence that R&D intensity is positively associated with firms' choices of auditors who specialize in auditing R&D contracts. Additionally, we find that R&D intensive firms tend to appoint top‐tier auditors. We use simultaneous equations to control for interrelationships between dependent variables in addition to single‐equation ordinary least squares (OLS) and logistic regression models. Our results are particularly strong in tests using samples of small firms whose auditor choice is not constrained by the need to appoint a top‐tier auditor to ensure the auditor's financial independence from the client.